2021
DOI: 10.3390/mi12101199
|View full text |Cite
|
Sign up to set email alerts
|

Solution for Mass Production of High-Throughput Digital Microfluidic Chip Based on a-Si TFT with In-Pixel Boost Circuit

Abstract: As one of the most popular research hotspot of lab-on-chip, digital microfluidic (DMF) technology based on the principle of electrowetting has unique advantages of high-precision, low cost and programmable control. However, due to the limitation of electrodes number, the throughput is hard to further upgrade. Therefore, active matrix electrowetting-on-dielectric (AM-EWOD) technology is a solution to acquire larger scale of driving electrodes. However, the process of manufacturing of AM-EWOD based on thin-film-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The device adopted polycrystalline silicon instead of amorphous silicon to achieve higher carrier mobility. In 2021, Qin et al from Nanjing University demonstrated an AM-DMF chip based on a-Si:H [62]. The pixels of the 32 × 32 matrix feature an integrated boost circuit that can raise the pixel voltage up by 50%.…”
Section: Tft Devices In Digital Microfluidic Chipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device adopted polycrystalline silicon instead of amorphous silicon to achieve higher carrier mobility. In 2021, Qin et al from Nanjing University demonstrated an AM-DMF chip based on a-Si:H [62]. The pixels of the 32 × 32 matrix feature an integrated boost circuit that can raise the pixel voltage up by 50%.…”
Section: Tft Devices In Digital Microfluidic Chipsmentioning
confidence: 99%
“…Reprinted, with permission, from [56]. (b) Layout and pixel schematics of the AM-DMF chip based on 3T2C.Reproduced from[62]. CC BY 4.0.…”
mentioning
confidence: 99%
“…Very recently, an emerging DMF device based on thin film transistors (TFTs) has also been reported. [27][28][29] Typically, it involves an active matrix of thousands of electrodes, with each electrode able to be addressed individually. Such features have promptly made the TFT-based DMF device a very hot topic, which has gained extensive interest in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…For the portable DMF platform, it may cause large volume, and the operation of multiple droplets is troublesome. Some researchers have used large-scale electrode arrays to improve the chip's ability to control droplets in parallel, 35,36 which helps to synchronize the experiment and shorten the experimental period. It is an essential direction for the development of DMF, 37 and facilitates high-throughput analysis on the DMF chip.…”
Section: Introductionmentioning
confidence: 99%